Does board size moderate the relationship between sustainability reporting and firm performance? - Jocelyn Mok Pau Chee; Mohd Ashari Bakri (ResearchGate, 2024)
The study aims to determine the moderating effect of board size on the relationship between sustainability reporting and corporate performance. The 200 largest Malaysian firms, based on market capitalization (2021), are examined for the period from 2012 to 2021. The study uses a pooled Ordinary Least Square (OLS), random, and fixed effects analysis. The results show that board size does not affect the relationship between sustainability reporting and firm performance. Moreover, the result is robust even after weakening the serial correlation and heteroskedasticity problem. The result suggests that board size plays a less significant role in influencing sustainability reporting and firm performance. Despite the less significant influence, board size should not be neglected as this variable is one of the most important determinants of corporate performance and should be further investigated in different contexts and variables.